PAN-Immobilized PVC-NPOE Membrane for Environmentally Friendly Sensing of Cd(II) Ions - Moersilah Moersilah; Dwi Siswanta; Roto Roto; Mudasir Mudasir (Indonesian Journal of Chemistry, 2017)
A simple, cheap and environmentally friendly analytical method of Cd(II) in the aqueous system has been developed by immobilization of 1-(2-pyridilazo)-2-naphtol (PAN) in poly vinyl chloride (PVC) matrix and nitrophenyl octyl ether (NPOE) as a plasticizer. Upon contact with Cd(II) in solution, the color of sensor membrane changes from dark yellow to dark red, which is due to the formation of Cd(II)–PAN complex. The best sensing results were obtained at pH 8.0 and λmax 558 nm. The dimension of the proposed sensor membrane was 0.8 cm x 2 cm with a thickness of 0.05 mm, the volume of sample was 2 mL with the Cd(II) concentration range of  0 – 1.2 ppm. The limit of detection of the method was found to be 0.432 + 0.104 ppm, which was reversible. The proposed methods have been applied in the determination of Cd(II) in water samples after addition of internal standard.